2017
DOI: 10.5152/eurasianjmed.2017.17132
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and its Association with Disease Severity in Psoriasis

Abstract: Objective: The main purpose of this research was to crosscheck sleep quality in patients with psoriasis with that in healthy individuals and to evaluate a possible relationship between sleep quality and disease severity in these patients. Materials and Methods:Fifty-eight patients with plaque psoriasis and 58 age-and gender-matched healthy individuals were included. The Psoriasis Area and Severity Index (PASI) scoring method was used to assess the disease severity in patients with psoriasis. The sleep quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
4
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 17 publications
(25 reference statements)
7
47
4
5
Order By: Relevance
“…Poor sleep quality was found to be significantly associated with rosacea with a high coefficient (OR, 3.525; 95% CI, 2.759–4.519). Moreover, there is a positive association between the severity of rosacea and sleep quality in our investigation, which is similar to the previous reports showing a positive association between PSQI and the severity of atopic dermatitis and psoriasis 43,46,50 . Our finding indicated that poor sleep quality is associated with rosacea, as well as its severity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Poor sleep quality was found to be significantly associated with rosacea with a high coefficient (OR, 3.525; 95% CI, 2.759–4.519). Moreover, there is a positive association between the severity of rosacea and sleep quality in our investigation, which is similar to the previous reports showing a positive association between PSQI and the severity of atopic dermatitis and psoriasis 43,46,50 . Our finding indicated that poor sleep quality is associated with rosacea, as well as its severity.…”
Section: Discussionsupporting
confidence: 91%
“…In our results, approximately 52.3% of rosacea patients suffered poor sleep quality (PSQI, >5), which is a decent proportion even compared with psoriasis. Meanwhile, the PSQI score in the rosacea patients is 6.20 ± 3.40, approaching that in psoriasis, 43,46,50 much higher than that of healthy controls (3.95 ± 2.63). Six of the seven PSQI components were found to be significantly higher in the rosacea group in our research, which is more than those in psoriasis 46 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The PSQI total score of 6.5 points for patients with HS in this study was significantly higher than for controls, and seems to be higher than among general populations evaluated in previous studies (28,29). Moreover, patients with other dermatoses, including AD and Ps, seem to have comparable mean PSQI scores, assessed as 7.0 and 7.0-9.2 points, respectively (21,30,31).…”
Section: Discussioncontrasting
confidence: 51%